GAMRASI SEBAGAI ATTRACTIVE LEARNING DALAM UPAYA MENUNJANG KEMAMPUAN LITERASI DAN NUMERASI SISWA - Fauzi, Fakhriza Ahmad; Mahanani, Enjang; Lusiani, Siska; Ernawati, Herni; Setyorini, Arifah Indah; Jana, Padrul (Universitas PGRI Yogyakarta, 2023)
It is hoped that GRAMASI learning media can help students improve their mathematical literacy and numeracy skills. Under these conditions, teachers are also required to be able to develop learning media that can facilitate student literacy and numeracy. This training activity aims to provide training and assistance to teachers, students, parents and guardians of class V students at SD Negeri Kemiri regarding the development of learning media containing mathematical literacy and numeracy questions consisting of question concepts and question characteristics. The method used is divided into seven stages, namely observing partner conditions (conditions, problems, needs), preparing activity agendas, creating GAMRASI learning media, socializing GAMRASI learning media in schools, applying GAMRASI learning media to students, analysis and evaluation, and final report. The 21 training participants were students, teachers, parents and guardians of students. Through this training activity, teachers can find out how the GAMRASI learning media works and can put it into practice. Keywords: GAMRASI, Literacy, Numeracy